Why do people use food banks? A qualitative study of food bank users in an English city. (17th December 2018) - Wainwright, David; Buckingham, Alan; Wainwright, Elaine
Abstract : The rise in the use of food banks has renewed debate about the extent of poverty and the adequacy of welfare provision. We conducted interviews with 25 food bank users in Bristol, England, finding that benefit penalties and precarious employment were implicated in food bank uptake, but that usage was more complicated than being an unmediated response to hunger. Food banks provided informal support for people on a low income to manage their food expenditure as well as meeting dietary needs. Some reported shame at needing the food bank, but others suggested that the informality and flexibility of food banks were preferable to some forms of state welfare.